2022
DOI: 10.3390/ijgi11060321
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Characteristics and Spatial Pattern of the Catering Industry in the Four Central Cities of the Yangtze River Delta

Abstract: The development of the catering industry in big cities is of great significance for countries to improve the quality of development and improve people’s living standards. In recent years, the urban catering industry has effectively promoted the process of urbanization, and it is significant to study the development characteristics and spatial distribution of the catering industry for the urban pattern. Taking the four central cities (Shanghai, Hangzhou, Nanjing, and Hefei) of China’s Yangtze River Delta (YRD) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…The spatial distribution and influencing factors of the foodservice industry have previously been studied from the perspective of tourism, mainly in the context of single foodservice formats such as hotels [ 11 ], tourist restaurants [ 12 ], fast food chains [ 13 ], and high-end restaurants [ 14 ]. As the availability of spatial data has increased, scholars have begun to use qualitative methods to study the spatial characteristics and influencing factors of the foodservice industry, which include transportation accessibility [ 15 ], economic development [ 16 ], population density [ 16 , 17 ], infrastructure [ 18 , 19 ], locational factors [ 20 ], market demand [ 21 ], supplier density [ 22 ], commercial land prices [ 23 ], size and cost [ 24 ], and restaurant type [ 25 ].…”
Section: Section 1: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The spatial distribution and influencing factors of the foodservice industry have previously been studied from the perspective of tourism, mainly in the context of single foodservice formats such as hotels [ 11 ], tourist restaurants [ 12 ], fast food chains [ 13 ], and high-end restaurants [ 14 ]. As the availability of spatial data has increased, scholars have begun to use qualitative methods to study the spatial characteristics and influencing factors of the foodservice industry, which include transportation accessibility [ 15 ], economic development [ 16 ], population density [ 16 , 17 ], infrastructure [ 18 , 19 ], locational factors [ 20 ], market demand [ 21 ], supplier density [ 22 ], commercial land prices [ 23 ], size and cost [ 24 ], and restaurant type [ 25 ].…”
Section: Section 1: Introductionmentioning
confidence: 99%
“…The kernel density estimation, cold hotspot analysis, spatial clustering and other methods have been used in these studies [ 15 , 26 ]. Quantitative analysis methods such as correlation analysis, geodetector software, and geographically weighted regressions have been used to explain the impacts of various factors on the spatial pattern in the foodservice industry [ 16 , 21 , 27 ]. Recently, the Online To Offline (O2O) model has dramatically changed the spatial distribution of restaurants in China.…”
Section: Section 1: Introductionmentioning
confidence: 99%
“…For example, joint promotion and mutual support among enterprises within catering clusters can enhance the visibility and brand image of the entire cluster [22]. Moreover, research has shown that the spatial relationships of urban and community catering clusters [23,24], the agglomeration process of catering clusters [25], and the variations in cluster size of different catering clusters [13] all contribute to regional economic development, including the creation of employment opportunities and tax revenue [8,14,26]. Catering clusters that are not severely affected by competition can elevate the visibility and appeal of the entire region, enticing more diners to patronize restaurants and bolstering the growth of the overall catering industry.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, scholars have explored various aspects of catering clusters using POI data, specifically the identification of catering clusters [23,31], the spatial distribution characteristics of catering clusters [16,32], the guidance of catering clusters for urban planning [33,34], the economic benefits of catering clusters [35,36], and the competition and cooperation of catering clusters [37,38] and the network relationships of catering clusters [39,40]. The emergence of POI data enables a clearer and more accurate analysis of the distribution of restaurant establishments, the development patterns of catering clusters, and the mechanisms of cluster evolution, whether viewed from a macro or micro perspective.…”
Section: Introductionmentioning
confidence: 99%
“…The current literature on the aggregation characteristics of urban commercial formats, including catering, can be divided into two main aspects. The first aspect concerns the spatial distribution of the urban commercial formats that can be identified through various methods and indicators such as KDE, Moran's I, Getis-Ord G*, and DBSCAN [5][6][7][8][9]. On this basis, analyses of different urban commercial formats' location choices have also been conducted.…”
Section: Introductionmentioning
confidence: 99%